Unravelling tertiary students’ ownership, usage, attitudes and preferences of mobile devices as tools for M-learning - Md. Ngadiran, Nurizah; Alias, Nor Aziah (Serials Publications, 2018)
Throughout educational institutions around the globe, mobile learning (M-learning) has become a growing field of practice and studies. The number of students that have access to mobile devices is also increasing from time to time. The purpose of this research is to determine the students’ present ownership and usage of mobile devices, find out the students’ attitudes towards the application of M-learning, and discover their preferences in the use of mobile devices for learning Academic English in future. A total of 164 students who enrolled in Academic English course from Universiti Tun Hussein Onn Malaysia, Johor (UTHM) had participated in the study. This research had deployed survey method and the data was obtained from a set of questionnaire. Statistical Package for Social Science (SPSS) software was used to analyze the data. The data was processed using descriptive statistics: frequencies, percentage, mean (M) and standard deviation (SD). The findings suggested that laptops and smartphones seem to be the devices being used by the students of this institution. The findings of this research also highlight that the students use mobile devices to conduct a wide-range of learning activities. To add, the results illustrate the encouraging opportunities in creating learning activities associated with mobile devices by the lecturers and institution.